Sexuality repositioned : diversity and the law - Brooks-Gordon, Belinda (Hart, 2004)
Despite the advent of new sexual knowledges, new perspectives, new experiences even, we do not routinely or habitually reflect on the interface of social and legal dimensions of sexuality. Rather, the law is periodically reviewed in response to some crisis or campaign. The idea for the book thus came from awareness that it is important to explore some of the social and moral censures, contours and controversies that shape and mark the boundaries of sexuality. The production of the book has coincided with a major review and new legislation concerning sexual offences, fuelling the authors' concer.